(untitled) (Research, Society and Development, 2022)
The aim of this study was to evaluate the color stability of the composite resin when subjected to different intensities of light curing and coloring substances. An in vitro study was carried out with samples (n=50) of microhybrid resin (Spectro Basic, Dentsply Sirona) randomized into 10 groups, according to the light curing distance (D1: 0 mm and D2: 8 mm) and the dye solutions (serum saline, coffee, grape juice, orange soda and tea). Data were tabulated and analyzed using IBM SPSS software. Tests were applied according to normality (Shapiro-Wilk test) and homoscedasticity (Levene test) and, after these analyses, the 1-way ANOVA test was performed with a repeated measure, followed by the Sidak post-test. The significance level was set at 5%. The differences between the initial and final color (ΔWID) were evaluated and the color change was expressed through the whitening index (WID). The immersion time of the samples in the substances was 2 months. The limits of perceptibility and acceptability were, respectively, 0.72 and 2.60 WID units. The values of psolutions, ptime and pdistance were significant (<0.0001). Higher ΔWID values were generally observed in the orange soda group (ΔWID = -52.19) and tea group (ΔWID -25.23). It was concluded that orange soda and tea were the drinks that most changed the color of the composite resin. And the light-curing distance that obtained the best color stability of the resin was 0 mm.